2019
DOI: 10.1051/0004-6361/201935865
|View full text |Cite
|
Sign up to set email alerts
|

Chemical complexity in high-mass star formation

Abstract: Aims. In order to understand the observed molecular diversity in high-mass star-forming regions, we have to determine the underlying physical and chemical structure of those regions at high angular resolution and over a range of evolutionary stages. Methods. We present a detailed observational and modeling study of the hot core VLA 3 in the high-mass star-forming region AFGL 2591, which is a target region of the NOrthern Extended Millimeter Array (NOEMA) large program CORE. Using NOEMA observations at 1.37 mm … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 124 publications
7
59
0
Order By: Relevance
“…While not as chemically rich as some other sources in the CORE sample (for example AFGL2591 or W3 OH/H 2 O, see Beuther et al 2018;Gieser et al 2019;Ahmadi et al 2018), the W3 IRS4 region does show a reasonable degree of chemical complexity, particularly at the position of IRS4 itself (see Fig. 14).…”
Section: Chemical Conditions In the W3irs4 Regionmentioning
confidence: 88%
“…While not as chemically rich as some other sources in the CORE sample (for example AFGL2591 or W3 OH/H 2 O, see Beuther et al 2018;Gieser et al 2019;Ahmadi et al 2018), the W3 IRS4 region does show a reasonable degree of chemical complexity, particularly at the position of IRS4 itself (see Fig. 14).…”
Section: Chemical Conditions In the W3irs4 Regionmentioning
confidence: 88%
“…Another factor may be the geometry of the masing region which can affect the beaming and therefore the brightness of the masers. It was found that beaming which is stronger than that given by Elitzur (1992) but similar to that found by Spaans & van Langevelde (1992) is needed to explain the observed brightness temperatures of the masers. However it should not be as strong as that used by Sobolev et al (1997).…”
Section: General Commentsmentioning
confidence: 73%
“…When a population inversion occurs, beaming becomes important in which case Eq. 3 becomes (Elitzur 1992) with Ω i j /4π the fractional beam solid angle. According to Elitzur (1992), Ω i j /4π = (2τ i j ) −1 .…”
Section: Numerical Methods and Molecular Datamentioning
confidence: 99%
See 2 more Smart Citations